2015
DOI: 10.11113/jt.v75.5243
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Compliance With Public Procurement Guidelines in the Nigerian Construction Industry

Abstract: The Nigerian Construction industry through its procurement activities is contributing immensely to the economic development of the country.Nigeriaas a developing nation is still working hard to strengthening the public procurement sector through which public infrastructural facilities are developed. Public Procurement Guidelines are the procedural manual guiding public procurement processes. The guidelines are as provided by the public procurement Act PPA 2007, since then compliance with the guidelines has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…This could explain why procurement policy ignorance ranks highest among the most significant influence factors. This concurs with Zadawa et al (2015), DiMaggio and Powell (2015), and Tabish and Jha (2015), who identified procurement policies as a significant factor influencing compliance with the standard of materials.…”
Section: Procurement-based Factors Influencing Compliance With Nation...supporting
confidence: 87%
See 2 more Smart Citations
“…This could explain why procurement policy ignorance ranks highest among the most significant influence factors. This concurs with Zadawa et al (2015), DiMaggio and Powell (2015), and Tabish and Jha (2015), who identified procurement policies as a significant factor influencing compliance with the standard of materials.…”
Section: Procurement-based Factors Influencing Compliance With Nation...supporting
confidence: 87%
“…Thus, deliberate changes in procurement policies affect professionals' compliance with national standards. This finding concurs with Zadawa et al (2015), which concluded that in Nigeria's public construction sector, misconception and unfamiliarity with procurement policies critically undermined compliance. Also, Mwelu et al (2018) observed that non-compliance is significantly induced by self-interest and weak enforcement mechanisms.…”
Section: Variables Reductionsupporting
confidence: 86%
See 1 more Smart Citation
“…To conclude, three pertinent examples are offered; the Netherland's municipalities experienced non-compliance with procurement procedures due to a lack of familiarity with procurement process itself (de Boer and Telgen, 1998). Similarly, in Nigeria's public construction sector, misconceptions and a lack of familiarity with procurement policies significantly affected compliance (Zadawa, Hussin and Osmadi, 2015) and finally reports showed a lack of familiarity with regulatory framework significantly affected compliance with Procurement Act in Kenya's public secondary schools' sector (Migosi et al, 2013).…”
Section: Familiarity With Regulatory Frameworkmentioning
confidence: 99%
“…For this reason, it was argued that the awareness of procurement regulation in state-owned enterprises is low (Sandada and Kambarami, 2016). Through a conceptual model, Zadawa et al (2015) highlighted the possible influence of familiarity with procurement guidelines on compliance with public procurement regulations.…”
Section: Familiarity Ethical Behavior Andcompliance With Public Procurement Regulationsmentioning
confidence: 99%